The Impact of Paternalistic Leadership on Innovative Work Behavior. A Test of Mediation Model. - Tayaba Patel; Haroon Bakari (ETIKONOMI, 2022)
Leadership is a paramount factor in enhancing employee innovation and creativity. This study aims to test the impact of paternalistic leadership (PL) on employees’ innovative work behavior (IWB) and to check the mediating role of employee Psychological Safety (PS). Using positivistic philosophy and a deductive approach, this study has employed a convenience sampling technique to collect data through questionnaires from 317 employees working in the Textile and IT industries. Partial Least Square Structural equation modeling (PLS-SEM) is used to analyze the data. Findings suggest that psychological safety was positively related to innovative work behavior and psychological safety mediated this link. This study is among very few studies that have tested the paternalistic leadership style in the innovative context of Pakistan. A major contribution for practitioners is to know that paternalistic leadership will enhance employee innovative work behavior through psychological safety. Moreover, data from the textile and software industries also increased the relevance and originality of this study.JEL Classification: J24, J28, O31, L67, L86